The Role of the Pegon Script as Islamic Pedagogy in Supporting Religious Education, Local Identity, and Faith-Based Literacy in Banten Islamic Boarding Schools - Nikmatullah, Cecep; Tihami, M.A; Badrudin, B; Tarihoran, Naf’an; Wasehudin, W (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study aims to examine the role of the Pegon Arabic Script in Islamic Religious Education learning at the Banten Islamic Boarding School, where in the process of translating the yellow book, mastery of nahwu and sharaf is absolutely necessary. However, both are considered difficult lessons for students to understand, including the translation process. This study uses a qualitative descriptive analytical approach through the case study research method. Data collection techniques through interviews, observations, and documentation, through data analysis techniques in the form of data reduction, data display, and data verification. From the results of the study, findings were obtained, where in the Islamic Religious Education learning process at the Banten Islamic Boarding School, including planning, implementation and evaluation. The Pegon Arabic Script plays a role and helps students in Islamic Religious Education learning, especially the process of translating the yellow book as teaching materials. Among its advantages, namely: all elements of the text are translated in more detail, vocabulary is wider, through symbols it can be easier, easier to understand the contents of the Yellow Book, appreciate the sense of language, and uniqueness that must be preserved. While the disadvantages are that it takes a long time to understand and requires a lot of teaching staff. Thus, the Pegon Arabic script can play a role and contribute to students in understanding the yellow book as a reference material for PAI learning at the Banten Islamic Boarding School.